2010
DOI: 10.1016/s2255-4971(15)30362-1
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Fractures in Total Knee Arthroplasty

Abstract: The increasing number of total knee arthroplasties, in combination with the population's longer life expectancy, has led to a greater number of long-term complications. These add to the poor bone quality of elderly patients and often culminate in periprosthetic fractures. This complex orthopedic problem has a great diversity of clinical presentation. It may affect any of the bones in the knee and, because of the difficulty in finding solutions, may lead to disastrous outcomes. Its treatment requires that ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…After a mean follow-up of 34 months, the Knee Society Score and Range of Motion were measured and their analysis showed that there was no impact on the outcome based on fracture type or treatment method. However, a significant correlation was revealed by the study, between the functional outcome (measured by the Knee Society Score) and the quality of life (evaluated with Short Form Health Survey [36], a selfadministered questionnaire).…”
Section: Articles Covering Femoral and Tibial Fractures After Tkamentioning
confidence: 81%
See 1 more Smart Citation
“…After a mean follow-up of 34 months, the Knee Society Score and Range of Motion were measured and their analysis showed that there was no impact on the outcome based on fracture type or treatment method. However, a significant correlation was revealed by the study, between the functional outcome (measured by the Knee Society Score) and the quality of life (evaluated with Short Form Health Survey [36], a selfadministered questionnaire).…”
Section: Articles Covering Femoral and Tibial Fractures After Tkamentioning
confidence: 81%
“…One of the most recent studies in our database was published in 2019, by Karam et al [36]. The authors focused on an uncovered topic in previous articles: the comparison between prosthetic and non-prosthetic femoral fractures, treated with locking plates, based on risk factors and postoperative outcome.…”
Section: New Perspectives On Periprosthetic Femoral Fracturesmentioning
confidence: 99%
“…However, not all surgeons have the expertise, training, and facilities to perform this microsurgical procedure, which limits its use in many trauma situations. Other good options, like allogenic bone grafts and bone graft substitutes, also have limited use mainly due to its high cost [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The associated use of autograft has been proposed as an osteogenic stimulus with good results reported [ 4 , 6 , 7 , 11 , 13 , 15 ]. Those authors describe the use of cancellous bone graft for augmentation of the fibular graft and speeding up the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of this technique over vascularised autografts are easier operative procedure, shorter operative time and remodeling capacity at the donor site. 3,4 Application of dynamic compression plates (DCP) has been suggested in the fracture of the shaft of femur as it allows early mobilization. However fracture of the shaft of femur with segmental bone loss required an augmentation technique, cortical strut graft used as increasing mechanical strength of the site of the fracture.…”
Section: Introductionmentioning
confidence: 99%